2014
DOI: 10.1038/cmi.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Soluble interleukin-6 receptor is elevated during influenza A virus infection and mediates the IL-6 and IL-32 inflammatory cytokine burst

Abstract: Influenza A virus (IAV) infection is a major worldwide public health problem. However, the factors involved in mediating the inflammatory response to this infection and their relationships remain poorly understood. Here, we show that IAV infection stimulates the expression of the soluble IL-6 receptor (sIL-6R), a multifunctional protein involved in IL-6 signaling. Interestingly, sIL-6R expression upregulated the levels of its own ligand, IL-6 and those of the pro-inflammatory cytokine IL-32. shRNA-mediated kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 51 publications
(61 reference statements)
1
42
0
Order By: Relevance
“…Accordingly, silencing of IL-32 up-regulated the expression of sIL-6Ra during influenza virus infection. Thus, IL-32 simultaneously decreased sIL-6Ra while enhancing IL-6 production [85]. These results indicate that during influenza A virus infections PGE 2 , NO, sIL-6Ra, and IL-32 are produced, and these proinflammatory mediators influence each other.…”
Section: The Role Of Il-32 In Viral Infectionsmentioning
confidence: 62%
“…Accordingly, silencing of IL-32 up-regulated the expression of sIL-6Ra during influenza virus infection. Thus, IL-32 simultaneously decreased sIL-6Ra while enhancing IL-6 production [85]. These results indicate that during influenza A virus infections PGE 2 , NO, sIL-6Ra, and IL-32 are produced, and these proinflammatory mediators influence each other.…”
Section: The Role Of Il-32 In Viral Infectionsmentioning
confidence: 62%
“…Signaling of IL6 via the sIL6R promotes proinflammatory activities (33). Recent studies have found that sIL6R expression up-regulates the levels of its own ligand IL6 as well as the proinflammatory cytokine IL32 (34), and the circulating sIL6R elicited extensive antiviral activity through the induction of type I and type III IFNs (25,26). Furthermore, sIL6R was found to facilitate the nuclear translocation of IRF3 and NF-B (25).…”
Section: Il6r Is a Target Of Mir-590-5pmentioning
confidence: 99%
“…51,52 Impaired healing in animal models and age-related delayed healing of acute human wounds exhibit raised local and systemic levels of TNFα that may parallel the proinflammatory phenotype. 53,54 The pleiotropic cytokine IL6 is produced by macrophages, dendritic cells, mast cells, and other innate immune cells; consequently, this cytokine has long been considered a marker of inflammation. 55 Using ELISA to detect the concentration of TNFα and IL6 at different times, results showed that PACT treatment inhibited inflammation-factor secretion, significantly reduce the scalded-tissue concentration of TNFα and IL6, and prevent further deepening of the wound.…”
mentioning
confidence: 99%